Surface excitations in the modelling of electron transport for electron-beam-induced deposition experiments - Salvat-Pujol, Francesc; Valentí, Roser; Werner, Wolfgang S. (Beilstein Journal of Nanotechnology, 2015)
The aim of the present overview article is to raise awareness of an essential aspect that is usually not accounted for in the modelling of electron transport for focused-electron-beam-induced deposition (FEBID) of nanostructures: Surface excitations are on the one hand responsible for a sizeable fraction of the intensity in reflection-electron-energy-loss spectra for primary electron energies of up to a few kiloelectronvolts and, on the other hand, they play a key role in the emission of secondary electrons from solids, regardless of the primary energy. In this overview work we present a general perspective of recent works on the subject of surface excitations and on low-energy electron transport, highlighting the most relevant aspects for the modelling of electron transport in FEBID simulations.
Keywords: focused-electron-beam-induced deposition (FEBID); Monte Carlo simulation of electron transport; surface excitations; secondary-electron emission

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Smith, D. A.; Fowlkes, J. D.; Rack, P. D. (Nanotechnology, 2007)

(untitled) - Silvis-Cividjian, N.; Hagen, C. W.; Kruit, P. (J. Appl. Phys., 2005)

(untitled) - Liu, Z.-Q.; Mitsuishi, K.; Furuya, K. (Nanotechnology, 2006)

(untitled) - Smith, D. A.; Fowlkes, J. D.; Rack, P. D. (Small, 2008)

(untitled) - Salvat-Pujol, F.; Jeschke, H. O.; Valentí, R. (Beilstein J. Nanotechnol., 2013)

(untitled) - Ritchie, R. H. (Phys. Rev., 1957)

(untitled) - Powell, C. J.; Swan, J. B. (Phys. Rev., 1959)

(untitled) - Powell, C. J.; Swan, J. B. (Phys. Rev., 1959)

(untitled) - Ritchie, R. H.; Marusak, A. L. (Surf. Sci., 1966)

(untitled) - Geiger, J. (Phys. Status Solidi, 1967)

(untitled) - Otto, A. (Phys. Status Solidi, 1967)

(untitled) - Kröger, E. (Z. Phys., 1968)

(untitled) - Kröger, E. (Z. Phys., 1970)

(untitled) - Chan, D.; Richmond, P. (Surf. Sci., 1973)

(untitled) - Jacob, J. H. (Phys. Rev. A, 1973)

(untitled) - Chan, D.; Richmond, P. (J. Phys. C, 1975)

(untitled) - Chan, D.; Richmond, P. (J. Phys. C, 1975)

(untitled) - Chan, D.; Richmond, P. (J. Phys. C, 1976)

(untitled) - Arista, N. R. (Phys. Rev. A, 1994)

(untitled) - Tung, C. J.; Chen, Y. F.; Kwei, C. M.; Chou, T. L. (Phys. Rev. B, 1994)

(untitled) - Chen, Y. F.; Kwei, C. M. (Surf. Sci., 1996)

(untitled) - Yubero, F.; Sanz, J. M.; Ramskov, B.; Tougaard, S. (Phys. Rev. B, 1996)

(untitled) - Denton, C.; Gervasoni, J. L.; Barrachina, R. O.; Arista, N. R. (Phys. Rev. A, 1998)

(untitled) - Ding, Z.-J. (J. Phys.: Condens. Matter, 1998)

(untitled) - Ding, Z.-J. (J. Phys.: Condens. Matter, 1998)

(untitled) - Kwei, C. M.; Wang, C. Y.; Tung, C. J. (Surf. Interface Anal., 1998)

(untitled) - Vicanek, M. (Surf. Sci., 1999)

(untitled) - Li, Y. C.; Tu, Y. H.; Kwei, C. M.; Tung, C. J. (Surf. Sci., 2005)

(untitled) - Salvat-Pujol, F.; Werner, W. S. M. (Surf. Interface Anal., 2013)

(untitled) - Da, B.; Mao, S. F.; Ding, Z. J. (J. Phys.: Condens. Matter, 2011)

(untitled) - Werner, W. S. M.; Glantschnig, K.; Ambrosch-Draxl, C. (J. Phys. Chem. Ref. Data, 2009)

(untitled) - Koepernik, K.; Eschrig, H. (Phys. Rev. B, 1999)

(untitled) - Ambrosch-Draxl, C.; Sofo, J. O. (Comput. Phys. Commun., 2006)

(untitled) - Lindhard, J. (Mat.-Fys. Medd. - K. Dan. Vidensk. Selsk., 1954)

(untitled) - Mermin, N. D. (Phys. Rev. B, 1970)

(untitled) - Denton, C. D.; Abril, I.; Garcia-Molina, R.; Moreno-Marín, J. C.; Heredia-Avalos, S. (Surf. Interface Anal., 2008)

(untitled) - Schattschneider, P.; Hébert, C.; Franco, H.; Jouffrey, B. (Phys. Rev. B, 2005)

(untitled) - Bote, D.; Salvat, F. (Phys. Rev. A, 2008)

Classical Electrodynamics - Jackson, J. D. (John Wiley & Sons, Inc., 1975)

Introduction to Electrodynamics - Griffiths, D. J. (Prentice Hall, 1999)

(untitled) - Nazarov, V. U. (Surf. Sci., 1995)

(untitled) - Werner, W. S. M.; Novák, M.; Salvat-Pujol, F.; Zemek, J.; Jiricek, P. (Phys. Rev. Lett., 2013)

(untitled) - Werner, W. S. M.; Tratnik, H.; Brenner, J.; Störi, H. (Surf. Sci., 2001)

(untitled) - Salvat-Pujol, F.; Werner, W. S. M.; Novák, M.; Jiricek, P.; Zemek, J. (Phys. Rev. B, 2014)

(untitled) - Werner, W. S. M. (Surf. Interface Anal., 2001)

(untitled) - Salvat, F.; Jablonski, A.; Powell, C. J. (Comput. Phys. Commun., 2005)

(untitled) - Bote, D.; Salvat, F.; Jablonski, A.; Powell, C. J. (J. Electron Spectrosc. Relat. Phenom., 2009)

(untitled) - Novák, M. (Surf. Sci., 2008)

(untitled) - Voreades, D. (Surf. Sci., 1976)

(untitled) - Pijper, F. J.; Kruit, P. (Phys. Rev. B, 1991)

(untitled) - Müllejans, H.; Bleloch, A. L. (Phys. Rev. B, 1992)

(untitled) - Müllejans, H.; Bleloch, A. L.; Howie, A.; Tomita, M. (Ultramicroscopy, 1993)

(untitled) - Werner, W. S. M.; Salvat-Pujol, F.; Bellissimo, A.; Khalid, R.; Smekal, W.; Novák, M.; Ruocco, A.; Stefani, G. (Phys. Rev. B, 2013)

(untitled) - Chung, M. S.; Everhart, T. E. (Phys. Rev. B, 1977)